Development and Validation of an Instrument to Assess Teacher Leadership Behaviors in a Math–Science Partnership Program. Issue 5 (September 2016) - Doraiswamy, Nithya; Porter, Kristen M.; Wilson, Grant; Paprzycki, Peter; Czerniak, Charlene M.; Tuttle, Nicole; Czajkowski, Kevin
This paper describes the development and validation of a science teacher leadership instrument modeled on the seven domains of the Teacher Leader Model (TLM) Standards (The Teacher Leadership Exploratory Consortium, 2011). Instrument development was part of National Science Foundation–funded Mathematics and Science Partnership (MSP) program that aimed to develop science teacher leaders through the use of Project-Based Science (PBS) in the context of renewable energy. Ratings of professional development sessions presented by teacher leaders to their peers were analyzed to assess whether the instrument could be used to measure teacher leadership in this context. The resulting TLM Standards Instrument is presented as a valid instrument to observe the development and assessment of teacher leadership.